2012
DOI: 10.1007/s00221-012-3023-x
|View full text |Cite
|
Sign up to set email alerts
|

Monocular learning of a spatial task enhances sleep in the right hemisphere of domestic chicks (Gallus gallus)

Abstract: Unihemispheric sleep is an aspect of cerebral lateralization of birds. During sleep, domestic chicks show brief periods during which one eye is open whilst the other remains shut. In this study, time spent in sleeping and in monocular-unihemispheric sleep (Mo-Un sleep) was investigated following the monocular learning of a spatial discrimination task. Two groups of experimental chicks from day 8 to day 11 post-hatching were trained in a spatial paradigm based on geometrical and topographical clues. One group p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…In domestic chicks, the USWS should be considered a kind of local sleep. 100 , 101 In pigeons, the monocular visual stimulation during BS deprivation elicited an increase of SWS and the slope of slow waves only in the hyperpallium connected with the stimulated eye (visually processing region) during recovery but not in the nonvisual mesopallium. 157 It is suggested that local SWS increase is correlated with local synaptic plastic changes associated with the learning task and with improvement in the task performance after sleep.…”
Section: Hemispheric Asymmetries In Bihemispheric Sleep: Local Sleepmentioning
confidence: 99%
See 2 more Smart Citations
“…In domestic chicks, the USWS should be considered a kind of local sleep. 100 , 101 In pigeons, the monocular visual stimulation during BS deprivation elicited an increase of SWS and the slope of slow waves only in the hyperpallium connected with the stimulated eye (visually processing region) during recovery but not in the nonvisual mesopallium. 157 It is suggested that local SWS increase is correlated with local synaptic plastic changes associated with the learning task and with improvement in the task performance after sleep.…”
Section: Hemispheric Asymmetries In Bihemispheric Sleep: Local Sleepmentioning
confidence: 99%
“…Another group of chicks subjected to a spatial task showed subsequently more right Un-Mo sleep (left eye closure) related to a prevalent engagement of the right hemisphere in the task. 99 101 …”
Section: Unihemispheric Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the mallards had one eye open and seemed to use this eye to monitor their environment (see below), such asymmetries were classified as unihemispheric NREM sleep. Based on the relationships between unilateral eye closure and interhemispheric asymmetries in SWA described in EEG studies, eye state alone has been used as an indicator of unihemispheric sleep in several behavioral studies (Ball et al, 1988; Mascetti and Vallortigara, 2001; Boerema et al, 2003; Nelini et al, 2010, 2012; Mascetti, 2016). Finally, the AI thresholds used in dolphins and seals were recently employed to classify NREM sleep as unihemispheric, asymmetric, or symmetric in great frigatebirds ( Fregata minor ) in the wild where eye state could not be monitored (Rattenborg et al, 2016).…”
Section: Local Aspects Of Nrem Sleepmentioning
confidence: 99%
“…In future studies, it would be interesting to determine whether NREM sleep time or intensity increase unilaterally following sleep deprivation of only one hemisphere while fur seals sleep unihemispherically in the water. Finally, although unihemispheric sleep deprivation has not been performed in birds, several behavioral studies in chicken chicks have shown small, but significant, changes in the time spent with only the left or right eye closed in response to treatments thought to selectively activate one hemisphere or the other (e.g., Mascetti et al, 2007; Nelini et al, 2010, 2012; Quercia et al, 2018; reviewed in Mascetti, 2016), suggesting that sleep may be homeostatically regulated independently in each hemisphere. It will be important for future studies to determine the extent to which these changes in eye state correlate with changes in hemispheric sleep measured electrophysiologically (see Lesku et al, 2011b).…”
Section: Local Aspects Of Nrem Sleepmentioning
confidence: 99%